First record and occurrence of Acraea terpsicore (linnaeus, 1758) (Lepidoptera: Nymphalidae) in Malaysian Borneo - Fatimah Abang,; Sabina Noor,; Ratnawati Hazali,; Hamady Dieng, (Pusat Sistematik Serangga, Fakulti Sains dan Teknologi, Universiti Kebangsaan Malaysia, 2016)
The Tawny Coster, Acraea terpsicore (Linnaeus, 1758) (Lepidoptera: Nymphalidae) is recorded from Malaysian Borneo for the first time based on three specimens collected in Samarahan, southwestern Sarawak on 15th March 2013. Originally distributed in India and Sri Lanka, A. terpsicore is now known to have expanded its geographical range southwards to Southeast Asia and Australia over the last three decades. However, prior to 2013, there was no record of its occurrence on Borneo. Preliminary results of our field tracking and observations of the species in Malaysian Borneo within the last three years indicated that this species has recently become established in western Borneo and expanded its area of distribution from Samarahan 200 km northwards to Sri Aman. Field observations of this butterfly and distribution map of the species on Borneo based on field visits from 2013-2016 are presented. This common Oriental butterfly species may expand its range of distribution further northwards to North Borneo.